2019
DOI: 10.1371/journal.pone.0222604
|View full text |Cite
|
Sign up to set email alerts
|

Detailed global modelling of soil organic carbon in cropland, grassland and forest soils

Abstract: Assessments of the global carbon (C) cycle typically rely on simplified models which consider large areas as homogeneous in terms of the response of soils to land use or consider very broad land classes. For example, “cropland” is typically modelled as an aggregation of distinct practices and individual crops over large regions. Here, we use the process-based Rothamsted soil Carbon Model (RothC model), which has a history of being successfully applied at a global scale, to calculate attainable SOC stocks and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 82 publications
0
40
0
Order By: Relevance
“…The SOCD, TOCD, SICD and TCD ranged from 4.73 to 25.12, 9.22 to 48.98, 1.00 to 21. 29 (2018) also expressed that the effect of land use on SOC was the most significant on topsoil. The variation in SOC is due to the variation in texture [54,55] and mineralogy [56,57] of soils.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SOCD, TOCD, SICD and TCD ranged from 4.73 to 25.12, 9.22 to 48.98, 1.00 to 21. 29 (2018) also expressed that the effect of land use on SOC was the most significant on topsoil. The variation in SOC is due to the variation in texture [54,55] and mineralogy [56,57] of soils.…”
Section: Resultsmentioning
confidence: 99%
“…These include measurement methods, data sources (SOC data and SOC environmental covariates) and their resolution and extent, the different periods of data collection, or using multiple modeling and evaluation strategies (Grunwald, 2009;Ogle et al2010;Stockmann et al2013). Thus, there is a need for study describing SOC spatial variability across local to global scales [25,26,27,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with our data about the long-term effects of the previous land use (under natural forest vegetation) visible in different SOC dynamics in long-term field experiments. Morais et al [32] simulated with the RothC model changes in the annual SOC stock in 2014-2100 (without a climate change effect) globally for all land use classes. They demonstrated that the conversion of forest to cropland generally results in SOC loss, and SOC loss is typically faster than SOC recovery.…”
Section: The Importance Of the Land Use Historymentioning
confidence: 99%
“…These results are consistent with our data about the long-term effect of deforestation visible in different SOC dynamics in the long-term field experiments. Morais et al [26] simulated with RothC model changes in the annual SOC stock in 2014-2100 (without climate change effect) globally for all land use classes. They demonstrated that the conversion of forest to cropland in general result in SOC loss, and, SOC loss is typically faster than SOC recovery.…”
Section: The Importance Of the Land Use Historymentioning
confidence: 99%